145 Giant Cell Tumors of Bone With Pulmonary Metastasis. (11th January 2018) - Sethi, Shenon; Reddy, Vijaya; Bitterman, Pincas; Gattuso, Paolo
Abstract: Introduction: Giant cell tumor of bone (GCTB) is a relatively rare, benign, but locally aggressive primary intramedullary tumor. Pulmonary metastasis is seen in 2%-3%. This is a retrospective review of the clinical presentation, long-term outcomes, and treatment of GCTB with pulmonary metastasis. Methods and Materials: Institutional surgical pathology records from 1993 to 2015 were searched for primary GCTB. Results: A total of 98 patients with GCTB were identified with a mean age of 38 years and male to female ratio of 1.6:1. Of these, 30 developed local recurrence, and four (two men, two women, mean age 35 years) developed lung metastasis. The tumor locations included a case each of femur, tibia, T12 vertebra, and ischium. All four patients underwent intralesional curettage/subtotal resection. Lung metastases were detected at a mean of 79 months after the treatment of bone lesions. Two patients had local recurrences prior to and one had recurrence following pulmonary metastasis. The pulmonary metastases were managed by wedge resections in all cases. The recurrences were treated by surgery (1/3), surgery with methotrexate (1/3), and radiation and denosumab (1/3). All patients with metastatic disease were alive and healthy at a mean follow-up of seven years. Conclusion: Incidence of pulmonary metastasis in GCTB is 4% and of local recurrence is 31%. Intralesional curettage/subtotal resection has similar risk of local recurrence (30%) as wide resection (29%) but may increase the risk of pulmonary metastasis. There is no association between metastasis and site of the primary bone lesion. Patients with pulmonary metastasis of GCTB seem to have good prognosis.